2017
DOI: 10.1111/cod.12836
|View full text |Cite
|
Sign up to set email alerts
|

Variation in aluminium patch test reactivity over time

Abstract: The patch test reactivity to aluminium varies over time. Aluminium-allergic individuals may have false-negative reactions. Therefore, retesting with aluminium should be considered when there is a strong suspicion of aluminium contact allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Patch testing with aluminium chloride hexahydrate 10% pet. with a second reading on D7 has been recommended, as has retesting if there is a negative test result and strong suspicion, because of possible false‐negative results . In our study, all cases with persistent itching nodules who were suspected to be allergic to aluminium reacted positively to aluminium chloride hexahydrate 2% pet.…”
Section: Discussionmentioning
confidence: 60%
“…Patch testing with aluminium chloride hexahydrate 10% pet. with a second reading on D7 has been recommended, as has retesting if there is a negative test result and strong suspicion, because of possible false‐negative results . In our study, all cases with persistent itching nodules who were suspected to be allergic to aluminium reacted positively to aluminium chloride hexahydrate 2% pet.…”
Section: Discussionmentioning
confidence: 60%
“…A recent Danish questionnaire study of 177 Al-allergic children and their parents compared with a reference group concluded that itching vaccination granulomas and Al allergy have a considerable negative impact on these children and their families, causing for instance, reduced adherence to vaccination programs and a lower score on overall life quality as compared to the reference group. 8 Contact allergy to Al is not easily diagnosed, as the elicitation threshold might be higher than the patch test substance used 9 and since there is a considerable individual over-time variation in patchtest results, 10 resulting in a high risk of false-negative results in Alallergic individuals. A recent study on 241 children with previous vaccine-induced itching nodules found that patch testing with 2% Al chloride hexahydrate in pet.…”
Section: Introductionmentioning
confidence: 99%
“…Contact allergy to Al is not easily diagnosed, as the elicitation threshold might be higher than the patch‐test substance used 9 and since there is a considerable individual over‐time variation in patch‐test results, 10 resulting in a high risk of false‐negative results in Al‐allergic individuals. A recent study on 241 children with previous vaccine‐induced itching nodules found that patch testing with 2% Al chloride hexahydrate in pet.…”
Section: Introductionmentioning
confidence: 99%
“…Patch test diagnosis can employ either aluminium lactate or aluminium chloride hexahydrate; the most appropriate test preparation is still being discussed. With both salts in various concentrations, Siemund et al noted a high variability over time upon re-testing; therefore, false-negative reactions are possible and repeat testing is recommended in case of strong suspicion of aluminium contact allergy [ 44 ]. A 50-year-old Spanish patient was patch tested to various metals before placement of a metal dental implant.…”
Section: Resultsmentioning
confidence: 99%